Consensus Recommendations on Sulfonylurea and Sulfonylurea Combinations in the Management of Type 2 Diabetes Mellitus – International Task Force - Kalra, Sanjay (Indian J Endocrinol Metab, 2018)
For decades, sulfonylureas (SUs) have been important drugs in the antidiabetic therapeutic armamentarium. They have been used as monotherapy as well as combination therapy. Focus on newer drugs and concerns about the risk of severe hypoglycemia and weight gain with some SUs have led to discussion on their safety and utility. It has to be borne in mind that the adverse events associated with SUs should not be ascribed to the whole class, as many modern SUs, such as glimepiride and gliclazide modified release, are associated with better safety profiles. Furthermore, individualization of treatment, using SUs in combination with other drugs, backed with careful monitoring and patient education, ensures maximum benefits with minimal side effects. The current guidelines, developed by experts from Africa, Asia, and the Middle East, promote the safe and smart use of SUs in combination with other glucose-lowering drugs.